Arabidopsis p24 [Delta] 5 and p24 [Delta] 9 facilitate coat protein I-dependent transport of the K/HDEL receptor ERD2 from the golgi to the endoplasmic reticulum - Montesinos, Juan Carlos; Robinson, David G. (The plant journal, 2014)
The p24 proteins belong to a family of type I membrane proteins which cycle between the endoplasmic reticulum (ER) and Golgi via coat protein I (COPI) and COPII vesicles. Current nomenclature classifies them into four subfamilies, although plant p24 proteins belong to either the p24β or the p24δ subfamilies. Here, we show that Arabidopsis p24δ5/δ9 and HDEL ligands shift the steady-state distribution of the K/HDEL receptor ERD2 from the Golgi to the ER. We also show that p24δ5/δ9 interact directly with ERD2. This interaction requires the Golgi dynamics (GOLD) domain in p24δ5 and is much higher at acidic than at neutral pH, consistent with both proteins interacting at the cis-Golgi. In addition, p24δ5 also inhibits the secretion of HDEL ligands, but not constitutive secretion, showing a role for p24δ5 in retrograde Golgi-to-ER transport. Both p24δ5 and ERD2 interact with ADP-ribosylation factor 1 (ARF1) and COPI subunits, mostly at acidic pH, consistent with COPI vesicles being involved in retrograde transport of both proteins. In contrast, both proteins interact with the COPII subunit Sec23, mostly at neutral pH, consistent with this interaction taking place at the ER for anterograde transport to the Golgi apparatus.
Gesehen am 25.07.2017